Extracellular vesicles: innovative cell-free solutions for wound repair - Eerdekens, Hanne; Pirlet, Elke; Willems, Sarah; Bronckaers, Annelies; Pincela Lins, Paula M. (Frontiers in Bioengineering and Biotechnology, 2025)
Chronic non-healing wounds are often associated with conditions such as diabetes and peripheral vascular disease, pose significant medical and socioeconomic challenges. Cell-based therapies have shown promise in promoting wound healing but have major drawbacks such as immunogenicity and tumor formation. As a result, recent research has shifted to the potential of extracellular vesicles (EVs) derived from these cells. EVs are nanosized lipid bilayer vesicles, naturally produced by all cell types, which facilitate intercellular communication and carry bioactive molecules, offering advantages such as low immunogenicity, negligible toxicity and the potential to be re-engineered. Recent evidence recognizes that during wound healing EVs are released from a wide range of cells including immune cells, skin cells, epithelial cells and platelets and they actively participate in wound repair. This review comprehensively summarizes the latest research on the function of EVs from endogenous cell types during the different phases of wound healing, thereby presenting interesting therapeutic targets. Additionally, it gives a critical overview of the current status of mesenchymal stem cell-derived EVs in wound treatment highlighting their tremendous therapeutic potential as a non-cellular of-the-shelf alternative in wound care.